Dinamika Pengembangan Karakter Santri Melalui Program Tahfidz di Asrama Darul Qur'an Mojokerto - Norma Ayu Lutfiani; Emi Lilawati; M. Aliyul Wafa (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Purpose: This study aims to analyze the dynamics of character development among santri through the Al-Qur'an tahfidz program at the Darul Qur'an Bidayatul Hidayah Dormitory in Mojokerto. Methodology/approach: This study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving santri, dormitory wardens, and parents. Findings: The tahfidz program is implemented through routine memorization submission (setoran) and a disciplined daily schedule. The continuous memorization process gradually cultivates values of independence, responsibility, and self-control among santri. Daily interaction with Qur'anic verses supports the development of inner peace, patience, and mental resilience. Character formation is further reinforced by the exemplary conduct of dormitory wardens and a periodic evaluation system that actively involves parents. Nevertheless, internal factors such as insufficient self-motivation and external factors including negative peer influence were identified as key challenges in the character development process. Practical implications: This study offers a replicable model for Islamic boarding schools and educational institutions in designing structured, tahfidz-based character education programs. Originality/value: This study contributes to the literature on character education by examining the specific dynamics through which a tahfidz program shapes santri personality within a dormitory environment.